Casting process of iron-copper alloy bracket casting for new energy automobile

Through ultrasonic treatment and ball milling of copper powder and iron powder mixture, combined with rare earth elements and boron and other fillers, and repair capsules and metal flux, the segregation and thermal stress problems of iron-copper alloy support castings are solved, and its mechanical properties and high Low temperature stability.

CN119114858APending Publication Date: 2024-12-13SHAOGUAN JINBAO FOUNDRY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411279152.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

During the solidification process of iron-copper alloy support castings for new energy vehicles, crack problems caused by metastable liquid phase separation, macroscopic segregation and thermal stress, resulting in uneven and unstable performance.

Method used

Using ultrasonic treatment and ball milling mixture of copper powder and iron powder, combined with rare earth elements such as lanthanum and cerium and boron, it is stirred and poured under a nitrogen environment through an intermediate frequency furnace, and further improves the uniformity and density of the alloy by repairing capsules and metal fluxes. and reduce grain boundary migration and thermal expansion differences.

Benefits of technology

It significantly improves the compatibility and deformation resistance of iron and copper alloys, reduces the occurrence of cracks in high-pressure environments, and improves the mechanical properties and high and low temperature stability of the castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005041110430000131
    Figure BDA0005041110430000131
Patent Text Reader

Abstract

The invention relates to a casting technology of an iron-copper alloy support casting for a new energy automobile, and belongs to the technical field of iron-copper alloy casting. According to the iron-copper alloy casting process, the filler A and the filler B are introduced to synergistically improve the iron-copper alloy casting process, through interaction of all the components, the uniformity and compactness of the interior of the iron-copper alloy are improved, the segregation phenomenon caused by poor compatibility is improved, accordingly, temperature shock or cracks generated in the high-pressure environment are reduced, and the performance of the iron-copper alloy is synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of iron-copper alloy casting, and relates to a casting process of an iron-copper alloy bracket casting for a new energy vehicle. Background Art

[0002] In modern industry, iron-copper alloys are widely used in machinery manufacturing, electronic equipment and other fields because of their certain strength and good conductivity. However, due to the limitations of their own performance, their application is still in the stage of continuous development and improvement. Taking the iron-copper alloy bracket casting of new energy vehicles as an example, iron-copper alloy, as an immiscible metal, will undergo metastable liquid phase separation during its solidification process, forming two liquid phase regions, namely copper-rich region and iron-rich region, which leads to serious macro-segregation after the alloy solidifies, resulting in uneven composition, organization and performance of the prepared alloy; furthermore, when the vehicle is subjected to complex stress conditions such as sudden acceleration, sudden braking, frequent steering and driving on bumpy roads during driving, the uneven distribution of the binding force between atoms in the mixed crystal structure makes it easier for the unstable atomic arrangement to change, which is prone to distortion and deformation in the long run; in addition, due to the different vibration frequencies and amplitudes of copper atoms and iron atoms in the iron-copper alloy, the temperature change is relatively large when they absorb or release the same amount of heat. When the temperature changes rapidly, the heat cannot be evenly transferred in time, and the local temperature difference is large, which further aggravates the thermal expansion difference between atoms in different regions, thereby greatly increasing the thermal stress. When the thermal stress exceeds the tolerance limit of the alloy, fine cracks will appear, and in severe cases, even cause the bracket casting to burst. Summary of the invention

[0003] The purpose of the present invention is to provide a casting process for an iron-copper alloy bracket casting for new energy vehicles. The various components in the present invention interact with each other to improve the uniformity and density inside the iron-copper alloy, improve the segregation phenomenon caused by poor compatibility, thereby reducing the generation of cracks under sudden temperature changes or high-pressure environments, and synergistically improving the performance of the iron-copper alloy.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A casting process for an iron-copper alloy bracket casting for a new energy vehicle, the casting process comprising the following steps:

[0006] (1) copper powder and iron powder are mixed and immersed in a treatment solution for ultrasonic treatment, and then dried and ball-milled to obtain powder A;

[0007] (2) Powder A is placed in a medium frequency furnace and stirred to obtain melt A;

[0008] (3) Add filler A into the furnace and stir to obtain melt B;

[0009] (4) Add filler B into the furnace and stir at variable speed to obtain alloy liquid;

[0010] (5) Under a nitrogen environment, the alloy liquid is poured into a mold, cooled to room temperature, and after the casting is solidified, it is demolded, ground, polished, and heat-treated. The casting is cooled in the furnace to obtain an iron-copper alloy bracket casting for new energy vehicles.

[0011] Furthermore, in step (1), the mass ratio of the copper powder to the iron powder is 8.4-9.3:0.7-1.6; the treatment liquid is obtained by mixing 1.5-3.5wt% of isopropyl tri(dioctyl pyrophosphate) titanate and the remainder of anhydrous ethanol; the parameters of the ultrasonic treatment are: ultrasonic frequency of 40-60kHz, ultrasonic temperature of 50-60°C, and ultrasonic time of 10-30min; the parameters of the ball milling step are: ball milling speed of 220-320rmp, and ball milling time of 3-5h.

[0012] Furthermore, the temperature of the medium frequency furnace in step (2) is 1100-1300° C.; the parameters of the stirring step are: stirring speed is 30-50 rpm, and stirring time is 30-40 min.

[0013] Furthermore, in step (3), the filler A accounts for 1.2-1.6wt% of the melt B; the parameters of the stirring step are: stirring speed is 50-70rmp, and stirring time is 1.2-1.8h.

[0014] Furthermore, the preparation method of the filler A is: after mixing 0.5-1.5 parts by weight of lanthanum, 0.3-1.2 parts by weight of cerium, 0.2-1 parts by weight of neodymium, 0.6-1.2 parts by weight of boron, 0.5-0.7 parts by weight of magnesium, 0.3-0.5 parts by weight of zinc sulfide, 0.3-0.5 parts by weight of para-hydroxyapatite and 0.5-0.8 parts by weight of sodium fluoroaluminate, setting the ball mill speed to 300-700 rpm, and ball milling for 1-2 hours to obtain filler A.

[0015] Furthermore, in step (4), the filler B accounts for 1.5-2.5wt% of the alloy liquid; and the variable speed stirring is first stirring at a speed of 600-1000 rpm for 20-30 min, and then stirring at 80-120 rpm for 1-2 h.

[0016] Furthermore, the preparation method of the filler B is: 2-3 parts by weight of a repair capsule, 0.6-0.8 parts by weight of a metal flux, 0.1-0.2 parts by weight of polyvinyl pyrrolidone, 0.02-0.1 parts by weight of sodium dodecylbenzene sulfonate, 0.5-0.7 parts by weight of magnesium, 0.5-0.8 parts by weight of sodium fluoroaluminate and 8-10 parts by weight of 50-60wt% ethanol are mixed, the ultrasonic frequency is set to 30-40kHz, the ultrasonic temperature is set to 40-50°C, ultrasonic stirring is performed for 20-30min, and drying is performed to obtain the filler B; wherein the metal flux is composed of 0.31-0.39 parts by weight of sodium chloride, 0.2-0.28 parts by weight of potassium chloride and 0.08-0.14 parts by weight of lithium chloride.

[0017] Furthermore, the preparation method of the repair capsule is:

[0018] a. ball-milling and magnetron sputtering mullite and mixing it with isopropyl tri(dioctyl pyrophosphate acyloxy) titanate in a mass ratio of 3.2-4.5:0.5-1.2 to obtain a shell material;

[0019] b. Mix 1.2-2.6 parts by weight of silicon powder having an average particle size of 5-35 μm and 6-12 parts by weight of 75-85 wt % ethanol solution, and stir at a speed of 1000-5000 rpm for 20-40 min to obtain a repair agent suspension;

[0020] c. Mix 2.5-3.5 parts by weight of shell material, 1.2-2 parts by weight of repair agent suspension, 0.03-0.05 parts by weight of potassium persulfate and 0.04-0.08 parts by weight of dibutyltin dilaurate, stir at 70-80°C and 700-900 rpm for 3.2-3.8 hours, centrifuge at 800-2000 rpm for 10-20 minutes, filter through 200 mesh filter cloth, wash the precipitate with deionized water, and dry in an oven at 70°C for 10 hours to obtain a repair capsule.

[0021] Furthermore, the parameters of the ball milling step are: the ball milling speed is 220-380 rpm, and the ball milling time is 2-4 hours; the magnetron sputtering is performed with alumina as the target material at a sputtering power of 100-200 W, and the deposition time is 30-60 minutes.

[0022] Furthermore, in step (5), the mold is preheated to 200-300°C; the pouring speed is 3-5kg / s; and the heat treatment is annealing the casting, first heating to 800-850°C and keeping warm for 2-3h, and then tempering at 400-500°C.

[0023] Beneficial effects of the present invention:

[0024] (1) The filler A of the present invention is composed of rare earth elements such as lanthanum and cerium, boron, zinc sulfide, para-hydroxyapatite and other components, wherein the unpaired electrons of the rare earth elements interact with the electrons of copper and iron atoms to form overlapping electron clouds, which play a bridging role at the iron-copper interface and promote the combination of iron and copper atoms; further, the rare earth elements are segregated at the grain boundaries, reduce the grain boundary energy, inhibit grain boundary migration and grain growth, thereby refining the grains and increasing the interphase area. The increase in the interphase area provides more channels and active sites for the mutual diffusion of copper and iron atoms, thereby improving the compatibility of the iron-copper alloy; in addition, boron can inhibit segregation by forming stable compounds with copper and iron, and zinc sulfide, para-hydroxyapatite and the like form fine dispersed phases in the alloy, which promote the uniform dispersion of different components by hindering the growth of matrix phase grains, reduce the occurrence of segregation, make the iron-copper alloy structure more uniform and stable, and thus improve the deformation resistance and crack resistance of the iron-copper alloy when the temperature changes.

[0025] (2) The orthorhombic crystal structure of mullite in the repair capsule of filler B of the present invention gives it a high melting point, high strength and good chemical stability. Alumina is deposited on its surface to form a solid protective film, which further enhances the stability and wear resistance of the shell material and prevents it from melting or deforming easily under high temperature conditions. Isopropyl tri(dioctyl pyrophosphate acyloxy) titanate can chemically bond with the surfaces of copper and iron powders as well as the surface of mullite. When cracks appear in the alloy, it plays a supporting role to prevent the further spread of the cracks. At the same time, silicon powder flows out and further fills the cracks by a small amount of aggregation or interaction with other components. The metal flux reduces the melting point of the alloy, improves the fluidity of the alloy, reduces the generation of defects in the alloy during the casting process, makes the alloy structure denser, and improves its resistance to sudden cooling and heating environments. Ingredients such as polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate promote the uniform dispersion of the components, avoid agglomeration, and synergistically improve the performance of the iron-copper alloy.

[0026] (3) The various components in the present invention interact with each other to improve the uniformity and density of the iron-copper alloy, improve the segregation phenomenon caused by poor compatibility, thereby reducing the generation of cracks under sudden temperature changes or high pressure environments, and synergistically improve the performance of the iron-copper alloy. DETAILED DESCRIPTION

[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0028] Example 1

[0029] A casting process for an iron-copper alloy bracket casting for a new energy vehicle, the casting process of this embodiment comprises the following steps:

[0030] (1) copper powder and iron powder are mixed and immersed in a treatment solution for ultrasonic treatment, and then dried and ball-milled to obtain powder A;

[0031] (2) Powder A is placed in a medium frequency furnace and stirred to obtain melt A;

[0032] (3) Add filler A into the furnace and stir to obtain melt B;

[0033] (4) Add filler B into the furnace and stir at variable speed to obtain alloy liquid;

[0034] (5) Under a nitrogen environment, the alloy liquid is poured into a mold, cooled to room temperature, and after the casting is solidified, it is demolded, ground, polished, and heat-treated. The casting is cooled in the furnace to obtain an iron-copper alloy bracket casting for new energy vehicles.

[0035] The mass ratio of copper powder to iron powder in step (1) of this embodiment is 8.4:0.7; the treatment liquid is obtained by mixing 1.5wt% isopropyl tri(dioctyl pyrophosphate) titanate and the remainder anhydrous ethanol; the parameters of the ultrasonic treatment are: ultrasonic frequency is 40kHz, ultrasonic temperature is 50°C, and ultrasonic time is 10min; the parameters of the ball milling step are: ball milling speed is 220rmp, and ball milling time is 3h.

[0036] The temperature of the medium frequency furnace in step (2) of this embodiment is 1100° C.; the parameters of the stirring step are: stirring speed is 30 rpm, and stirring time is 30 min.

[0037] In step (3) of this embodiment, filler A accounts for 1.2 wt% of melt B; the parameters of the stirring step are: stirring speed is 50 rpm, and stirring time is 1.2 h.

[0038] The preparation method of filler A in this embodiment is as follows: 0.5 weight parts of lanthanum, 0.3 weight parts of cerium, 0.2 weight parts of neodymium, 0.6 weight parts of boron, 0.5 weight parts of magnesium, 0.3 weight parts of zinc sulfide, 0.3 weight parts of p-hydroxyapatite and 0.5 weight parts of sodium fluoroaluminate are mixed, the ball mill speed is set to 300 rpm, and the ball mill is performed for 1 hour to obtain filler A.

[0039] In step (4) of this embodiment, filler B accounts for 1.5 wt% of the alloy liquid; variable speed stirring is first stirring at 600 rpm for 20 min, and then stirring at 80 rpm for 1 h.

[0040] The preparation method of filler B in this embodiment is as follows: 2 parts by weight of repair capsules, 0.6 parts by weight of metal flux, 0.1 parts by weight of polyvinyl pyrrolidone, 0.02 parts by weight of sodium dodecylbenzene sulfonate, 0.5 parts by weight of magnesium, 0.5 parts by weight of sodium fluoroaluminate and 8 parts by weight of 50wt% ethanol are mixed, the ultrasonic frequency is set to 30kHz, the ultrasonic temperature is set to 40°C, ultrasonic stirring is performed for 20 minutes, and drying is performed to obtain filler B; wherein the metal flux is composed of 0.31 parts by weight of sodium chloride, 0.2 parts by weight of potassium chloride and 0.08 parts by weight of lithium chloride.

[0041] The preparation method of the repair capsule of this embodiment is:

[0042] a. ball-milling and magnetron sputtering mullite and mixing it with isopropyl tri(dioctyl pyrophosphate) titanate in a mass ratio of 3.2:0.5 to obtain a shell material;

[0043] b. 1.2 parts by weight of silicon powder having an average particle size of 5 μm and 6 parts by weight of 75 wt % ethanol solution were mixed, and the mixture was stirred at a speed of 1000 rpm for 20 min to obtain a repair agent suspension;

[0044] c. Mix 2.5 parts by weight of shell material, 1.2 parts by weight of repair agent suspension, 0.03 parts by weight of potassium persulfate and 0.04 parts by weight of dibutyltin dilaurate, stir at 70°C and 700 rpm for 3.2 h, centrifuge at 800 rpm for 10 min, filter through 200 mesh filter cloth, wash the precipitate with deionized water, and dry in an oven at 70°C for 10 h to obtain repair capsules.

[0045] The parameters of the ball milling step in this embodiment are: the ball milling speed is 220 rpm, and the ball milling time is 2 hours; the magnetron sputtering is performed with aluminum oxide as the target material at a sputtering power of 100 W, and the deposition time is 30 minutes.

[0046] In step (5) of this embodiment, the mold is preheated to 200°C; the pouring speed is 3kg / s; the heat treatment is to anneal the casting, first heating to 800°C and keeping it warm for 2-3h, and then tempering at 400°C.

[0047] Example 2

[0048] A casting process for an iron-copper alloy bracket casting for a new energy vehicle, the casting process of this embodiment comprises the following steps:

[0049] (1) copper powder and iron powder are mixed and immersed in a treatment solution for ultrasonic treatment, and then dried and ball-milled to obtain powder A;

[0050] (2) Powder A is placed in a medium frequency furnace and stirred to obtain melt A;

[0051] (3) Add filler A into the furnace and stir to obtain melt B;

[0052] (4) Add filler B into the furnace and stir at variable speed to obtain alloy liquid;

[0053] (5) Under a nitrogen environment, the alloy liquid is poured into a mold, cooled to room temperature, and after the casting is solidified, it is demolded, ground, polished, and heat-treated. The casting is cooled in the furnace to obtain an iron-copper alloy bracket casting for new energy vehicles.

[0054] The mass ratio of copper powder to iron powder in step (1) of this embodiment is 9.3:1.6; the treatment liquid is obtained by mixing 3.5wt% isopropyl tri(dioctyl pyrophosphate) titanate and the remainder anhydrous ethanol; the parameters of the ultrasonic treatment are: ultrasonic frequency of 60kHz, ultrasonic temperature of 60°C, and ultrasonic time of 30min; the parameters of the ball milling step are: ball milling speed of 320rmp, and ball milling time of 5h.

[0055] The temperature of the medium frequency furnace in step (2) of this embodiment is 1300° C.; the parameters of the stirring step are: stirring speed is 50 rpm, and stirring time is 40 min.

[0056] In step (3) of this embodiment, filler A accounts for 1.6 wt% of melt B; the parameters of the stirring step are: stirring speed is 70 rpm, and stirring time is 1.8 h.

[0057] The preparation method of filler A in this embodiment is as follows: 1.5 parts by weight of lanthanum, 1.2 parts by weight of cerium, 1 part by weight of neodymium, 1.2 parts by weight of boron, 0.7 parts by weight of magnesium, 0.5 parts by weight of zinc sulfide, 0.5 parts by weight of p-hydroxyapatite and 0.8 parts by weight of sodium fluoroaluminate are mixed, the ball mill speed is set to 700 rpm, and the ball mill is performed for 2 hours to obtain filler A.

[0058] In step (4) of this embodiment, filler B accounts for 2.5 wt% of the alloy liquid; variable speed stirring is first stirring at a speed of 1000 rpm for 30 min, and then stirring at 120 rpm for 2 h.

[0059] The preparation method of filler B in this embodiment is as follows: 3 parts by weight of repair capsules, 0.8 parts by weight of metal flux, 0.2 parts by weight of polyvinyl pyrrolidone, 0.1 parts by weight of sodium dodecylbenzene sulfonate, 0.7 parts by weight of magnesium, 0.8 parts by weight of sodium fluoroaluminate and 10 parts by weight of 60wt% ethanol are mixed, the ultrasonic frequency is set to 40kHz, the ultrasonic temperature is set to 50°C, ultrasonic stirring is performed for 30 minutes, and drying is performed to obtain filler B; wherein the metal flux is composed of 0.39 parts by weight of sodium chloride, 0.28 parts by weight of potassium chloride and 0.14 parts by weight of lithium chloride.

[0060] The preparation method of the repair capsule of this embodiment is:

[0061] a. ball-milling and magnetron sputtering mullite and mixing it with isopropyl tri(dioctyl pyrophosphate) titanate in a mass ratio of 4.5:1.2 to obtain a shell material;

[0062] b. Mix 2.6 parts by weight of silicon powder having an average particle size of 35 μm and 12 parts by weight of 85 wt % ethanol solution, and stir at 5000 rpm for 40 min to obtain a repair agent suspension;

[0063] c. 3.5 parts by weight of shell material, 2 parts by weight of repair agent suspension, 0.05 parts by weight of potassium persulfate and 0.08 parts by weight of dibutyltin dilaurate were mixed, stirred at 80°C and 900 rpm for 3.8 h, centrifuged at 2000 rpm for 20 min, filtered through a 200-mesh filter cloth, washed with deionized water, and dried in an oven at 70°C for 10 h to obtain repair capsules.

[0064] The parameters of the ball milling step in this embodiment are: the ball milling speed is 380 rpm, and the ball milling time is 4 hours; the magnetron sputtering is performed with aluminum oxide as the target material at a sputtering power of 200 W, and the deposition time is 60 minutes.

[0065] In step (5) of this embodiment, the mold is preheated to 300°C; the pouring speed is 5kg / s; the heat treatment is to anneal the casting, first heating to 850°C and keeping it warm for 3h, and then tempering at 500°C.

[0066] Example 3

[0067] A casting process for an iron-copper alloy bracket casting for a new energy vehicle, the casting process of this embodiment comprises the following steps:

[0068] (1) copper powder and iron powder are mixed and immersed in a treatment solution for ultrasonic treatment, and then dried and ball-milled to obtain powder A;

[0069] (2) Powder A is placed in a medium frequency furnace and stirred to obtain melt A;

[0070] (3) Add filler A into the furnace and stir to obtain melt B;

[0071] (4) Add filler B into the furnace and stir at variable speed to obtain alloy liquid;

[0072] (5) Under a nitrogen environment, the alloy liquid is poured into a mold, cooled to room temperature, and after the casting is solidified, it is demolded, ground, polished, and heat-treated. The casting is cooled in the furnace to obtain an iron-copper alloy bracket casting for new energy vehicles.

[0073] The mass ratio of copper powder to iron powder in step (1) of this embodiment is 8.85:1.15; the treatment liquid is obtained by mixing 2.5wt% isopropyl tri(dioctyl pyrophosphate) titanate and the remainder anhydrous ethanol; the parameters of the ultrasonic treatment are: ultrasonic frequency is 50kHz, ultrasonic temperature is 55°C, and ultrasonic time is 20min; the parameters of the ball milling step are: ball milling speed is 270rmp, and ball milling time is 4h.

[0074] The temperature of the medium frequency furnace in step (2) of this embodiment is 1200° C.; the parameters of the stirring step are: stirring speed is 40 rpm, and stirring time is 35 min.

[0075] In step (3) of this embodiment, filler A accounts for 1.4 wt% of melt B; the parameters of the stirring step are: stirring speed is 60 rpm, and stirring time is 1.5 h.

[0076] The preparation method of filler A in this embodiment is as follows: 1 part by weight of lanthanum, 0.75 part by weight of cerium, 0.6 part by weight of neodymium, 0.9 part by weight of boron, 0.6 part by weight of magnesium, 0.4 part by weight of zinc sulfide, 0.4 part by weight of p-hydroxyapatite and 0.65 part by weight of sodium fluoroaluminate are mixed, the ball mill speed is set to 500 rpm, and the ball mill is performed for 1.5 hours to obtain filler A.

[0077] In step (4) of this embodiment, filler B accounts for 2 wt% of the alloy liquid; variable speed stirring is first stirring at 800 rpm for 25 min, and then stirring at 100 rpm for 1.5 h.

[0078] The preparation method of filler B in this embodiment is as follows: 2.5 parts by weight of repair capsule, 0.7 parts by weight of metal flux, 0.15 parts by weight of polyvinyl pyrrolidone, 0.06 parts by weight of sodium dodecylbenzene sulfonate, 0.6 parts by weight of magnesium, 0.65 parts by weight of sodium fluoroaluminate and 9 parts by weight of 55wt% ethanol are mixed, the ultrasonic frequency is set to 35kHz, the ultrasonic temperature is set to 45°C, ultrasonic stirring is performed for 25 minutes, and drying is performed to obtain filler B; wherein the metal flux is composed of 0.35 parts by weight of sodium chloride, 0.24 parts by weight of potassium chloride and 0.11 parts by weight of lithium chloride.

[0079] The preparation method of the repair capsule of this embodiment is:

[0080] a. ball-milling and magnetron sputtering mullite and mixing it with isopropyl tri(dioctyl pyrophosphate acyloxy) titanate in a mass ratio of 3.85:0.85 to obtain a shell material;

[0081] b. 1.9 parts by weight of silicon powder having an average particle size of 20 μm and 9 parts by weight of 80 wt % ethanol solution were mixed, and the mixture was stirred at 3000 rpm for 30 min to obtain a repair agent suspension;

[0082] c. Mix 3 parts by weight of shell material, 1.6 parts by weight of repair agent suspension, 0.04 parts by weight of potassium persulfate and 0.06 parts by weight of dibutyltin dilaurate, stir at 75°C and 800 rpm for 3.5 hours, centrifuge at 1400 rpm for 15 minutes, filter through 200 mesh filter cloth, wash the precipitate with deionized water, and dry in an oven at 70°C for 10 hours to obtain repair capsules.

[0083] The parameters of the ball milling step in this embodiment are: the ball milling speed is 300 rpm, and the ball milling time is 3 hours; the magnetron sputtering is performed with aluminum oxide as the target material at a sputtering power of 150 W, and the deposition time is 45 minutes.

[0084] In step (5) of this embodiment, the mold is preheated to 250°C; the pouring speed is 4kg / s; the heat treatment is to anneal the casting, first heating to 825°C and keeping it warm for 2.5h, and then tempering at 450°C.

[0085] Comparative Example 1

[0086] On the basis of Example 3, the step of treating with the treatment liquid is removed, and other conditions are the same as those in Example 3.

[0087] Comparative Example 2

[0088] On the basis of Example 3, filler A was removed and replaced with lanthanum of equal weight, and other conditions were consistent with Example 3.

[0089] Comparative Example 3

[0090] On the basis of Example 3, the repair capsules in filler B were removed and replaced with an equal weight of 55wt% ethanol solution. Other conditions were consistent with Example 3.

[0091] Comparative Example 4

[0092] On the basis of Example 3, the metal flux in filler B was removed and replaced with an equal weight of 55 wt % ethanol solution. Other conditions were the same as those in Example 3.

[0093] Comparative Example 5

[0094] On the basis of Example 3, the mullite is not ball-milled, and other conditions are consistent with those in Example 3.

[0095] Comparative Example 6

[0096] On the basis of Example 3, the mullite is not subjected to magnetron sputtering, and other conditions are consistent with those of Example 3.

[0097] Comparative Example 7

[0098] On the basis of Example 3, the isopropyl tri(dioctyl pyrophosphate) titanate in the repair capsule was removed and replaced with an equal weight of 80 wt % ethanol solution. Other conditions were consistent with Example 3.

[0099] Comparative Example 8

[0100] On the basis of Example 3, the heat treatment step after pouring is removed, and other conditions are consistent with Example 3.

[0101] 1. Performance testing

[0102] The iron-copper alloy bracket castings prepared in Examples 1-3 and Comparative Examples 1-8 were made into 30mm×10mm×10mm specimens, the tensile rate was set to 2mm / min, and the tensile strength (MPa) and yield strength (MPa) of the castings were tested according to standard GB / T9449-2008. The average values ​​are recorded as shown in Table 1.

[0103] Table 1

[0104] Tensile strength(MPa) Yield strength(MPa) Example 1 591 433 Example 2 608 451 Example 3 621 465 Comparative Example 1 552 489 Comparative Example 2 483 420 Comparative Example 3 423 237 Comparative Example 4 476 402 Comparative Example 5 455 281 Comparative Example 6 439 260 Comparative Example 7 532 468 Comparative Example 8 497 433

[0105] It can be seen from Table 1 that the tensile strength of the iron-copper alloy bracket castings prepared in Examples 1-3 is ≥591 MPa, and the yield strength is ≥433 MPa, both of which are better than the iron-copper alloy bracket castings prepared in Comparative Examples 1-8, indicating that the iron-copper alloy castings prepared in the present invention have good compatibility between the components and have good mechanical properties.

[0106] 2. High and low temperature performance test

[0107] The iron-copper alloy bracket castings prepared in Examples 1-3 were processed into samples of 10 mm × 10 mm × 6 mm. The samples were heated to 200°C at a rate of 5°C / min and maintained for 2 h, and then cooled to -40°C at a rate of 3°C / min and maintained for 2 h. After repeating 10 times, it was recorded whether the samples had bursting or cracking phenomena. The test results are shown in Table 2.

[0108] Table 2

[0109]

[0110]

[0111] As can be seen from Table 2, the iron-copper alloy bracket castings prepared in Examples 1-3 are still relatively stable in performance under alternating hot and cold environments, and no bursting or cracking occurs. In the present invention, various pre-treatments and post-processing are used to allow the components to interact with each other, improve the uniformity and density inside the iron-copper alloy, and improve the segregation phenomenon caused by poor compatibility. On this basis, components such as repair capsules and metal flux are introduced to effectively fill and repair cracks, reduce the generation of cracks under sudden temperature changes or high-pressure environments, and synergistically improve the performance of the iron-copper alloy.

[0112] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A casting process for an iron-copper alloy bracket casting for a new energy vehicle, characterized in that: The casting process comprises the following steps: (1) copper powder and iron powder are mixed and immersed in a treatment solution for ultrasonic treatment, and then dried and ball-milled to obtain powder A; (2) Powder A is placed in a medium frequency furnace and stirred to obtain melt A; (3) Add filler A into the furnace and stir to obtain melt B; (4) Add filler B into the furnace and stir at variable speed to obtain alloy liquid; (5) Under a nitrogen environment, the alloy liquid is poured into a mold, cooled to room temperature, and after the casting is solidified, it is demolded, ground, polished, and heat-treated. The casting is cooled in the furnace to obtain an iron-copper alloy bracket casting for new energy vehicles.

2. The casting process of the iron-copper alloy bracket casting for new energy vehicles according to claim 1 is characterized in that: In step (1), the mass ratio of the copper powder to the iron powder is 8.4-9.3:0.7-1.6; the treatment liquid is obtained by mixing 1.5-3.5wt% of isopropyl tri(dioctyl pyrophosphate) titanate and the remainder of anhydrous ethanol; the parameters of the ultrasonic treatment are: ultrasonic frequency of 40-60kHz, ultrasonic temperature of 50-60°C, and ultrasonic time of 10-30min; the parameters of the ball milling step are: ball milling speed of 220-320rmp, and ball milling time of 3-5h.

3. The casting process of the iron-copper alloy bracket casting for new energy vehicles according to claim 1 is characterized in that: The temperature of the medium frequency furnace in step (2) is 1100-1300° C.; the parameters of the stirring step are: stirring speed is 30-50 rpm, and stirring time is 30-40 min.

4. The casting process of the iron-copper alloy bracket casting for new energy vehicles according to claim 1 is characterized in that: In step (3), the filler A accounts for 1.2-1.6wt% of the melt B; the parameters of the stirring step are: stirring speed is 50-70rmp, and stirring time is 1.2-1.8h.

5. The casting process of the iron-copper alloy bracket casting for new energy vehicles according to claim 4 is characterized in that: The preparation method of the filler A is as follows: 0.5-1.5 parts by weight of lanthanum, 0.3-1.2 parts by weight of cerium, 0.2-1 parts by weight of neodymium, 0.6-1.2 parts by weight of boron, 0.5-0.7 parts by weight of magnesium, 0.3-0.5 parts by weight of zinc sulfide, 0.3-0.5 parts by weight of p-hydroxyapatite and 0.5-0.8 parts by weight of sodium fluoroaluminate are mixed, the ball milling speed is set to 300-700 rpm, and the ball milling is performed for 1-2 hours to obtain the filler A.

6. The casting process of the iron-copper alloy bracket casting for new energy vehicles according to claim 1 is characterized in that: In step (4), the filler B accounts for 1.5-2.5wt% of the alloy liquid; the variable speed stirring is first stirring at a speed of 600-1000rmp for 20-30min, and then stirring at 80-120rmp for 1-2h.

7. The casting process of the iron-copper alloy bracket casting for new energy vehicles according to claim 1 is characterized in that: The preparation method of the filler B is as follows: 2-3 parts by weight of a repair capsule, 0.6-0.8 parts by weight of a metal flux, 0.1-0.2 parts by weight of polyvinyl pyrrolidone, 0.02-0.1 parts by weight of sodium dodecylbenzene sulfonate, 0.5-0.7 parts by weight of magnesium, 0.5-0.8 parts by weight of sodium fluoroaluminate and 8-10 parts by weight of 50-60wt% ethanol are mixed, and the ultrasonic frequency is set to 30-40kHz, the ultrasonic temperature is set to 40-50°C, ultrasonic stirring is performed for 20-30min, and drying is performed to obtain the filler B; wherein the metal flux is composed of 0.31-0.39 parts by weight of sodium chloride, 0.2-0.28 parts by weight of potassium chloride and 0.08-0.14 parts by weight of lithium chloride.

8. The casting process of the iron-copper alloy bracket casting for new energy vehicles according to claim 7 is characterized in that: The preparation method of the repair capsule is as follows: a. ball-milling and magnetron sputtering mullite and mixing it with isopropyl tri(dioctyl pyrophosphate acyloxy) titanate in a mass ratio of 3.2-4.5:0.5-1.2 to obtain a shell material; b. Mix 1.2-2.6 parts by weight of silicon powder having an average particle size of 5-35 μm and 6-12 parts by weight of 75-85 wt % ethanol solution, and stir at a speed of 1000-5000 rpm for 20-40 min to obtain a repair agent suspension; c. Mix 2.5-3.5 parts by weight of shell material, 1.2-2 parts by weight of repair agent suspension, 0.03-0.05 parts by weight of potassium persulfate and 0.04-0.08 parts by weight of dibutyltin dilaurate, stir at 70-80°C and 700-900 rpm for 3.2-3.8 hours, centrifuge at 800-2000 rpm for 10-20 minutes, filter through 200 mesh filter cloth, wash the precipitate with deionized water, and dry in an oven at 70°C for 10 hours to obtain a repair capsule.

9. The casting process of the iron-copper alloy bracket casting for new energy vehicles according to claim 8, characterized in that: The parameters of the ball milling step are: the ball milling speed is 220-380 rpm, and the ball milling time is 2-4 hours; the magnetron sputtering is performed with aluminum oxide as the target material at a sputtering power of 100-200 W, and the deposition time is 30-60 minutes.

10. The casting process of the iron-copper alloy bracket casting for new energy vehicles according to claim 1, characterized in that: In step (5), the mold is preheated to 200-300°C; the pouring speed is 3-5kg / s; the heat treatment is to anneal the casting, first heating it to 800-850°C and keeping it warm for 2-3h, and then tempering it at 400-500°C.